Comparative time-series analyses of gut microbiome profiles in genetically and chemically induced lupus-prone mice and the impacts of fecal transplantation - Piraya Chatthanathon; Asada Leelahavanichkul; Thanya Cheibchalard; Alisa Wilantho; Nattiya Hirankarn; Naraporn Somboonna (Scientific Reports)
Abstract Although the association between gut dysbiosis (imbalance of the microbiota) in systemic lupus erythematosus (SLE) is well-known, the simultaneous exploration in gut dysbiosis in fecal and different intestinal sections before and after lupus onset (at 2, 4, 6, 8, and 10 months old) resulting from the loss of inhibitory Fc gamma receptor IIb (FcGIIb) and pristane induction have never been conducted. Anti-dsDNA (an important lupus autoantibody) and proteinuria developed as early as 6 months old in both models, with higher levels in FcGRIIb deficient (FcGRIIb-/-) mice. Compared to the healthy control at 2 and 4 months, the lupus mice (both FcGRRIIb-/- and pristane) and healthy mice at 6 months old demonstrated an alteration as indicated by the Shannon alpha diversity index, highlighting influences of lupus- and age-induced dysbiosis, respectively. Non-metric multidimensional scaling (NMDS) revealed that the fecal microbiota of FcGRIIb-/- mice were distinct from the age-matched healthy control at all timepoints (at 6 month, p < 0.05), while pristane mice showed divergence at only some timepoints. Analyses of different intestinal sections revealed similarity among microbiota in the cecum, colon, and feces, contrasting with those in the small intestines (duodenum, jejunum, and ileum). Subtle differences were found between FcGRIIb-/- and pristane mice in feces and the intestinal sections as assessed by several analyses, for examples, the similar or dissimilar distances (NMDS), the neighbor-joining clustering, and the potential metabolisms (KEGG pathway analysis). Due to the differences between the gut microbiota (feces and intestinal sections) in the lupus mice and the healthy control, rebalancing of the microbiota using rectal administration of feces from the healthy control (fecal transplantation; FMT) to 7-month-old FcGIIb-/- mice (the established lupus; positive anti-dsDNA and proteinuria) was performed. In comparison to FcGRIIb-/- mice without FMT, FMT mice (more effect on the female than the male mice) showed the lower anti-dsDNA levels with similar fecal microbiome diversity (16s DNA gene copy number) and microbiota patterns to the healthy control. In conclusion, gut microbiota (feces and intestinal sections) of lupus mice (FcGRIIb-/- and pristane) diverged from the control as early as 4–6 months old, correlating with lupus characteristics (anti-dsDNA and proteinuria). The different gut microbiota in FcGRIIb-/- and pristane suggested a possible different gut microbiota in lupus with various molecular causes. Furthermore, FMT appeared to mitigate gut dysbiosis and reduce anti-dsDNA, supporting the benefit of the rebalancing gut microbiota in lupus, with more studies are warranted.